Probiotics as Renal Guardians: Modulating Gut Microbiota to Combat Diabetes-Induced Kidney Damage - Saleh Bakheet Al-Ghamdi (Biology)
Gut microbiota plays a pivotal role in various health challenges, particularly in mitigating diabetes-induced renal damage. Numerous studies have highlighted that modifying gut microbiota is a promising therapeutic strategy for preserving kidney function and mitigating diabetes-related complications. This study aimed to evaluate the protective effects of Lactobacillus acidophilus ATCC 4356 supplementations on kidney health in a rat model of diabetes-induced renal damage. Four groups were studied: control, probiotic supplementation, diabetic, and diabetic with probiotic supplementation. Diabetes was induced using a single streptozotocin (STZ) injection after a 12 h fast, and probiotic supplementation (1 × 10⁹ CFU/kg daily) was administered two weeks prior to diabetes induction and continued throughout the experimental period. Weekly assessments included fasting blood glucose, insulin, glycation markers, and kidney function tests. Glucose metabolism and insulin sensitivity were analyzed through oral glucose tolerance test (OGTT) and insulin sensitivity test (IST). The microbiome was analyzed using 16S rRNA gene sequencing to evaluate changes in diversity and composition. Probiotic supplementation significantly enhanced microbial diversity and composition. Alpha diversity indices such as Shannon and Chao1 demonstrated higher values in the probiotic-treated diabetic group compared to untreated diabetic rats. The Firmicutes/Bacteroidetes ratio, a key indicator of gut health, was also restored in the probiotic-treated diabetic group. Results: Probiotic supplementation significantly improved glycemic control, reduced fasting blood glucose levels, and enhanced insulin sensitivity in diabetic rats. Antioxidant enzyme levels, depleted in untreated diabetic rats, were restored, reflecting reduced oxidative stress. Histological analysis showed better kidney structure, reduced inflammation, and decreased fibrosis. Furthermore, the Comet assay results confirmed a reduction in DNA damage in probiotic-treated diabetic rats. Conclusion: Lactobacillus acidophilus ATCC 4356 supplementation demonstrated significant protective effects against diabetes-induced renal damage by restoring gut microbiota diversity, improving glycemic control, and reducing oxidative stress. These findings highlight the potential of targeting the gut microbiota and its systemic effects on kidney health as a therapeutic approach for managing diabetes-related complications. Further research is needed to optimize probiotic treatments and assess their long-term benefits in diabetes management and kidney health.